Purified acetaminophen-glutathione conjugate is able to induce oxidative stress in rat liver mitochondria - Roušar, T; Nýdlová, E; Česla, P; Staňková, P; Kučera, O; Pařík, P; Červinková, Z (Physiological research, 2012)
Acetaminophen overdose is the most often cause of acute liver injury. The toxic mechanism is linked to formation of an active metabolite that reacts with glutathione generating acetaminophen-glutathione conjugate (APAP-SG). This compound has been recognized to be non-toxic generally. Our preliminary results showed, however, that APAP-SG could possess a toxic effect too. Therefore, the aim of our study was to prepare, purify and to test possible toxicity of APAP-SG. We prepared APAP-SG using organic synthesis. The conjugate was purified by preparative HPLC and its structure was confirmed using mass spectrometry. Final purity of APAP-SG was >98 %. We estimated a toxic effect of APAP-SG in isolated rat liver mitochondria using a fluorescent ROS probe. We assessed ROS production in presence of complex I or complex II substrates. The increase of ROS-dependent fluorescence in presence of glutamate/malate was 104 ± 13 % and 130 ± 10 % in 1 mM and 5 mM APAP-SG, respectively, in comparison with controls. ROS production related to presence of complex II substrate was enhanced 4-times in APAP-SG (5 mM) treated mitochondria (compared to controls). We conclude, we proved our hypothesis that APAP-SG conjugate is able to induce a mitochondrial impairment leading to enhanced ROS production.
Keywords: vztah mezi dávkou a účinkem léčiva; Rats; zvířata; reaktivní formy kyslíku; Mitochondria, Liver; mužské pohlaví; kyselina glutamová; Malates; Rats, Wistar; potkani Wistar; Glutamic Acid; Liver; Acetaminophen; játra; Chemical and Drug Induced Liver Injury; Animals; Reactive Oxygen Species; maláty; oxidační stres; modely nemocí na zvířatech; Dose-Response Relationship, Drug; Male; jaterní mitochondrie; Oxidative Stress; krysa rodu Rattus; paracetamol; Disease Models, Animal; lékové postižení jater